(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The article reveals the essence of the contract for division of inheritance through a set of its defining features: 1) it is concluded after the expiry of the period for acceptance of the inheritance, but before the heirs receive a certificate of inheritance; 2) the parties are the heirs who have accepted the inheritance in the manner and within the time limits specified by civil law; 3) it has a much smaller, auxiliary value compared to the role of a civil law contract, as it generates legal consequences in conjunction with other legal facts; 4) in the presence of a nasciturus, the contract may be concluded only after the birth of a child; 5) the division of the inheritance is carried out taking into account the preemptive right of individual heirs to receive inheritance property in kind. An inheritance division agreement belongs to the group of agreements in the field of inheritance law, and its subject matter is inheritance as an object of civil rights. The legal document for inheritance is not the agreement on the division of inheritance, but the certificate of the right to inheritance, issued by a notary for the execution of this agreement. Based on the legislative construction of Art. 1278 of the Civil Code of Ukraine it has been stated that the method of dividing the inheritance is the allocation of a share in kind, as a result of which the ideal share in the inheritance turns into a real one. The agreement on the division of the inheritance can be concluded by the heirs regardless of the type of inheritance, in particular, by will or by law. The contract under study may contain a condition for changing the size of the inheritance shares. However, the heirs cannot change the size of their shares in the inheritance if the testator personally set them in the will. In the presence of a will, priority should be given to the will of the testator, which cannot be changed by the heirs. Otherwise, the principle of freedom of will be violated. It is no coincidence that Art. 1267 of the Civil Code of Ukraine, which determines the change in the size of shares in the inheritance, is structurally placed in Chapter 86 “Inheritance by law”.